Analisa Kandungan Mineral, Lemak dan Protein pada Sampel Ikan Kembung Rebus Asin - Leni Widiarti; Sajaratud Dur (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Sumatera Utara, 2022)
Research has been carried out to analyze the content of minerals, fat and protein in salted boiled pufferfish samples. Samples were purchased from a traditional market in Medan City, Indonesia. The method used is the 2005 AOAC method. Crude protein analysis was carried out by the Kjeldhal method, crude fat analysis was carried out by the Soxhlet extraction method, water content analysis was carried out by the drying method, ash content analysis was carried out by the combustion method at high temperature, and mineral analysis was carried out by using an Atomic Absorption Spectrophotometer (AAS). The results of the analysis of the salted mackerel sample obtained crude protein content of 65.9770 %, this indicates that the salted boiled mackerel sample has a high protein content. Crude fat content from the analysis is 16.7600 %. The water content and ash content of the boiled mackerel samples were 9.5077% and 6.2700%, respectively. Mineral analysis, namely the levels of calcium and sodium obtained respectively 0.7635 ppm and 0.7571 ppm.